2016
DOI: 10.1371/journal.pone.0153225
|View full text |Cite
|
Sign up to set email alerts
|

Pumping Iron in Australia: Prevalence, Trends and Sociodemographic Correlates of Muscle Strengthening Activity Participation from a National Sample of 195,926 Adults

Abstract: ObjectiveThe current Australian Physical Activity Guidelines recommend that adults engage in regular muscle-strengthening activity (e.g. strength or resistance training). However, public health surveillance studies describing the patterns and trends of population-level muscle-strengthening activity participation are sparse. The aim of this study is to examine the prevalence, trends and sociodemographic correlates of muscle-strengthening activity participation in a national-representative sample of Australians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 26 publications
(40 reference statements)
8
85
6
Order By: Relevance
“…This is largely because adherence to the muscle strengthening guideline was low, at 28.9%. However, this is still higher than a recent Australian study, which found that the prevalence of sufficient muscle strengthening activity (defined as two or more sessions per week) in adults in the previous 2 weeks was only 10.4% …”
Section: Discussioncontrasting
confidence: 56%
“…This is largely because adherence to the muscle strengthening guideline was low, at 28.9%. However, this is still higher than a recent Australian study, which found that the prevalence of sufficient muscle strengthening activity (defined as two or more sessions per week) in adults in the previous 2 weeks was only 10.4% …”
Section: Discussioncontrasting
confidence: 56%
“…Unfortunately, most peri‐urban Australians do not reap the substantial health benefits attributable to physical activity, with only 36% being sufficiently active (ie, participated in at least 150 min of physical activity over a given week, including moderate and vigorous intensity activity, and walking for transport and fitness) . Even fewer meet the recommendations regarding activities specifically for muscle strengthening . Peri‐urban Australians are also sedentary for an average of 35.2 h per week .…”
Section: Introductionmentioning
confidence: 75%
“…While this is a sensible first step, an examination of how factors may interact to predict participation in RT is needed. In one study, age and socioeconomic status interacted when explaining participation in RT,17 and it is likely there are other relevant interactions. Modelling participation in RT beyond the traditional social-cognitive paradigm may also be useful,100 for example, assessing RT habits since building routines around participation was a frequently reported aspect of successful adoption of RT 35.…”
Section: Discussionmentioning
confidence: 99%